Landasan Teori Hukum Hak Pengembalian Barang Tanpa Alasan Dalam E-commerce - Yue Guan; Eni Oktaviani (Iuris Studia: Jurnal Kajian Hukum, 2020)
In the e-commerce environment, right of withdrawal is more accurately called right to return goods without reason. Although right to return goods without reason violates the strict pacta sunt servanda principle in civil law, the problems caused by the rapid development of e-commerce have prompted many countries to pay more attention to granting consumers right to return goods without reason. From a legal perspective, barriers to the formation of consumer intentions when signing consumption contracts with business actors, for the purpose of pursuing true freedom of contract, as well as providing protection to these vulnerable consumers, are all legal theoretical foundations of the system of right to return goods without reason